Fabrication and Characterization of Green-Synthesized Zinc Oxide Nanoparticles Loaded into Dissolving Microneedles: A Potential Delivery Platform for Breast Cancer Therapy - Haneen Faris Al-Shawabkeh; Rafa Aburayya; Haneen A. Basheer; Ahlam Zaid Alkilani; Maram A. Alhusban; Rania Hamed (ACS Omega, 2026)
Abstract Green-synthesized zinc oxide nanoparticles (ZnO NPs) can be used to explore their anticancer applications. Therefore, this study aimed to synthesize ZnO NPs using an eco-friendly method by combining Phoenix dactylifera (P. dactylifera) root hair extract with 0.8 M zinc acetate dihydrate at a volume ratio of 4:1. The ZnO NPs had an average size of 24.01 ± 1.70 nm, a polydispersity index (PDI) of 0.25 ± 0.02, and a zeta potential of −18.45 ± 1.80 mV. The X-ray diffraction analysis revealed the crystalline structure of ZnO NPs, and the energy-dispersive spectroscopy analysis showed zinc and oxygen compositions of 43.64% and 31.60%, respectively, confirming the formation of green-synthesized ZnO NPs. The ZnO NPs were then incorporated into dissolving microneedles (MNs) prepared using 10% sodium carboxymethyl cellulose (Na CMC). Additionally, doxorubicin hydrochloride (DOX), a chemotherapeutic agent used to treat breast cancer, was also loaded into MNs (DOX-loaded MNs). The ZnO NP- and DOX-loaded MNs were evaluated for morphology, mechanical properties, needle insertion, dissolution rate, recovery of ZnO and DOX, FTIR, ex vivo permeation, and stability. Both types of MNs exhibited a pyramidal shape with a square base, were capable of withstanding a compression force of 32 N for 30 s, pierced the Parafilm M sheet at a depth of 378–504 μm, and dissolved completely within 30 min. The ZnO NP-loaded MNs remained stable for 2 weeks at room temperature and in the refrigerator. Whereas DOX-loaded MNs remained stable for up to 1 week at room temperature and 2 weeks in the refrigerator. In vitro cytotoxicity studies showed that green-synthesized ZnO NPs reduced the viability of breast cancer cells; however, these studies evaluated free ZnO NPs rather than the MN formulation itself. In conclusion, MNs demonstrated a promising platform for enhancing the transdermal delivery of green-synthesized ZnO NPs and DOX, representing a novel approach combining P. dactylifera-derived ZnO nanoparticles with dissolving microneedle-based delivery.